A handbook on the use of FADN database in programming models - Sebastian Neuenfeldt; Alexander Gocht (Johann Heinrich von Thünen-Institut, 2014)
The main objective of the current report is to provide a guideline on how the farm accountancy data network (FADN) can be employed in mathematical programming models. The reader of this report is introduced to the FADN database to become familiar with the underlying rules and specific issues.
urn:nbn:de:gbv:253-201412-dn054328-2
Keywords: 630